Tradisi Manjapuik Batu dan Manampuang sebagai Bagian dari Budaya Lokal Masyarakat Nagari Gadut - Puan Nabilla; Elida Elida; Yuliarma Yuliarma (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study examines the local culture of Nagari Gadut as preserved through the traditions of Manjapuik Batu and Manampuang. The main issue addressed in this research is the limited written documentation and academic studies on these traditions, which are predominantly transmitted orally and are vulnerable to changes in meaning over time. The purpose of this study is to describe the implementation, cultural meanings, and social functions of Manjapuik Batu and Manampuang within the community of Nagari Gadut. This research employs a qualitative approach, with data collected through literature review, direct observation, and in-depth interviews with traditional leaders and local community members. The data were analyzed using descriptive qualitative analysis to interpret the values and meanings of the traditions from the perspective of the supporting community. The findings indicate that the Manjapuik Batu tradition functions as a customary practice related to death rituals, emphasizing values of mutual cooperation, togetherness, and adherence to adat norms. Meanwhile, the Manampuang tradition reflects social solidarity, discipline, and principles of equality through the equal distribution of sacrificial meat to all participants. The study concludes that both traditions serve not only as local cultural heritage but also as value systems that shape the social character of the Nagari Gadut community and therefore need to be documented as part of cultural preservation efforts.